Influence of arm position on ultrasound visibility of the axillary brachial plexus. Issue 11 (November 2015) - Frkovic, Vedran; Ward, Catherine; Preckel, Benedikt; Lirk, Phillip; Hollmann, Markus W.; Stevens, Markus F.; Wegener, Jessica T.
Abstract : BACKGROUND: Contemporary axillary brachial plexus block is performed by separate injections targeting radial, median, ulnar and musculocutaneous nerve. These nerves are arranged around the axillary artery, making ultrasound visualisation sometimes challenging. In particular, the radial nerve can be difficult to localise deep to the artery. OBJECTIVES: The primary aim of this study was to investigate which arm position optimises the visibility of the radial nerve. Secondary aims were the visibility and position of the other nerves during varying arm positions. DESIGN: A prospective observational study. SETTING: University teaching hospital, November 2012. PARTICIPANTS: Twenty volunteers, recruited by an advertisement on the Department's bulletin board. Inclusion criterion age more than 18 years. Exclusion criteria: refusal of ultrasound examination, restricted shoulder movement, local infection, BMI greater than 30 kg m –2 . INTERVENTION: One anaesthesiologist performed bilateral ultrasound examinations of the axillary brachial plexus on 20 volunteers. Each arm was placed in different positions [shoulder (S) 90° or 180° abduction, elbow (E) 0° or 90° extension] and scans were performed proximally in the axilla, and additionally 5 cm distally to this point [proximal (P) vs. distal (D)], resulting in eight different scans stored for off-line analysis performed by two blinded anaesthesiologists. MAIN OUTCOME MEASURES: For radial, median, ulnar and musculocutaneous nerve, visibility was assessed on a six-point visibility scale. Distances and angles of the nerves relative to the axillary artery and distances relative to the skin were measured. RESULTS: No significant differences between arm positions were found in the visibility score of radial ( P = 0.359) and musculocutaneous nerves ( P = 0.073). Visibility of the median nerve was improved in positions S90°/E0°/D and S180°/E0°/P ( P = 0.02). The ulnar nerve was more visible in position S180°/E 0°/P and D ( P = 0.007). The greatest distance between artery and radial nerve was 7.4 ± 4.7 mm at an angle of 120 ± 14° in position S180°/E 0°/D. CONCLUSION: The visibility of the radial nerve was not improved by varying positions of the arm. S180°/E0° provided the best overall visibility and accessibility of nerves. TRIAL REGISTRATION: https://www.toetsingonline.nl/to/ccmo_search.nsf/Searchform?OpenForm Identifier: NL42116.018.12.